From spaces of sexual violence to sites of networked resistance: re-imagining mobile and social media technologies - Hart, Laurel; Mitchell, Claudia (Faculty of Education, University of the Free State, 2015)
To date, much of the work on mobile and social media in the context of sexual violence has focused on its threats and harmful effects, particularly in relation to cyber-bullying and other forms of online harassment. But what if we think of such technologies as technologies of non-violence? In this article we make a case for exploring this work in rural South Africa, where, in spite of some challenges of access, the availability of technology is increasing the number of possible ways of addressing sexual violence. Building on what we offer as a primer of technologies currently available, we consider the implications of this work for researchers (especially those in education), interested in how technology can help to address sexual violence.
Keywords: Cellphones; Technologies of non-violence; Rurality; Sexual violence; Mobile apps; Social networks; Information and communication technologies